Interactions between diatoms and fine sediment. Issue 3 (30th December 2012) - Jones, J. I.; Duerdoth, C. P.; Collins, A. L.; Naden, P. S.; Sear, D. A.
Abstract Excessive mobilization and delivery of fine sediments to water bodies has detrimental impacts on those biotic elements used for waterbody status classification, including macroinvertebrates, fish and macrophytes. The relationship between fine sediment and diatoms is a reciprocal one, with diatoms influencing the production and retention of fine sediments, as well as being impacted by fine sediment derived from the catchment. Diatoms can increase the retention of fine sediments in benthic environments as a result of various mechanisms, including shear stress modification, surface adhesion and bed clogging. Enhanced retention of fines can have important implications for the transfer and fate of sediment‐associated nutrients and contaminants. Excessive fine sediment loadings impact diatom assemblages via shading, burial and scouring. Indirect impacts of increased fine sediment stress can result from changes in habitat availability, herbivory or predator changes, which cascade down the food chain. Indices based on the relative abundance of motile species have been proposed for using diatoms to assess waterbody status. However, disentangling the potential confounding impacts of alternative environmental stressors on these simplistic indices remains a significant challenge. Coupling sediment pressure models, capable of predicting the potential impact of mitigation, with meaningful diatom‐based indices, remains a challenge for catchment planning for sediment abatement and the attainment of improved, or protection of, ecological status. Existing targets for sediment management in river catchments are largely based on relationships between sediment stress and impacts on fish, but these thresholds have been widely criticized. There remains a need to develop generic modelling toolkits coupling sediment stress and impacts on a range of biological quality elements to support a weight‐of‐evidence approach. Copyright © 2012 John Wiley & Sons, Ltd.